COLLABORATIVE GOVERNANCE IN AN EFFORT TO TRAFFIC AND ROAD TRANSPORTATION SAFETY IN SEMARANG CITY - Tilano, Fawwaz Aldi; Suwitri, Sri (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2019)
The number of accidents that occurred in Indonesia continues to grow each year is no exception Semarang City, to decrease the number of accidents that happen takes the role of stakeholders in the implementation of traffic and road transportation safety through collaboration because each stakeholder can’t work alone. The purpose of this research was to know how the collaboration of stakeholders in the implementation of traffic and road transportation safety and analyze the factors driving and inhibiting the collaboration. The writer used the model of collaborative governance from Ansell and Gash, and De Seve. The method of this study was descriptive qualitative research method. The instruments for collecting the data were interviews, literature study, observation, and documentation. The results showed collaborative governance in the implementation of traffic safety and road transport in Semarang seen first conditions, institutional design, and collaborative process has been running well, but not optimal implementation of facilitative leadership. The driving factor which affects the collaboration that is networked structure, commitment to a common purpose, distributive accountability/responsibility, and information sharing, while the only factor inhibiting access to the resource. The recommendations given are implementing more maximal facilitative leadership by leveraging existing LLAJ Forum and held a contract employee recruitment and planning more effective and efficient.